Short Communication: Identification and characterization of nitrifying bacteria in mud crab (Scylla serrata) recirculation aquaculture system by 16S rRNA sequencing - YUNI PUJI HASTUTI; IMAN RUSMANA; KUKUH NIRMALA; RIDWAN AFFANDI; SISKA TRIDESIANTI (Society for Indonesian Biodiversity, 2019)
Abstract. Hastuti YP, Rusmana I, Nirmala K, Affandi R, Tridesianti S. 2019. Identification and characterization of nitrifying bacteria in mud crab (Scylla serrata) recirculation aquaculture system by 16S rRNA sequencing. Biodiversitas 20: 1339-1343. Recirculation is one of the systems used for increasing aquaculture production, for example, is mud crab Scylla serrata culture. Aquaculture activities will produce organic nitrogen waste and can be affected to inorganic condition (nitrification bacteria). Nitrifying bacteria are capable of changing aerobically from NH4+ to NO2-(nitrite) and from NO2-to NO3-(nitrate). This current work aimed to identify and characterize nitrifying bacteria in mud crab (S. serrata) culture with a recirculated system. Nitrifying bacteria were isolated using serial dilution (10-1 until 10-5) of open filter FB water sample previously cultured in a specific medium. Bacterial identification was performed using a procedure of PrestoTM Mini gDNA Kit (Geneid) for DNA extraction and Polymerase Chain Reaction (PCR) primer 63F and 1387R for 16S rRNA gene amplification. Molecular identification using 16S rRNA sequences, the nitrifying bacteria isolated from mud crab recirculation aquaculture system were 99% identified as a group Pantoea calida, Pseudomonas stutzerii dan Halomonas sp. Morphological characterization of the colony morphology showed that a mucoid appearance and appeared cream in color and large size. Furthermore, their cells were recognized as basil and Gram-negative.